Legal review of the Soreang Religious Court Decision on Divorce Suit of A Soldier's Wife in The Army Without Permission from The Unit Commander (Case Study of the Soreang Religious Court Decision Number 363/Pdt.G/2021/PA.Sor) - Agung Sigit Purwanto (Goodwood Publishing, 2023)
Purpose: This study aims to analyze the legal procedures related to divorce lawsuits filed by the wives of Indonesian Army soldiers without permission from the Unit Commander. Research Methodology: The author uses a normative legal approach. According to Soerjono Soekanto, a normative legal approach is a legal research conducted by examining library materials or secondary data as basic materials for research by conducting a search for regulations and literature related to the problems being studied. Results: The results of the author's research found that there had been a Divorce Suit filed by the wife of an Indonesian Army soldier against her husband without permission from the Commander and was considered not in accordance with procedures in the soldier's environment, but the facts on the ground by the Soreang Religious Court the case was still processed and decided. This happens because there is a lack of synchronization regarding the granting of a letter of permission from superiors/officials where the TNI Commander Regulation Number 50 of 2014 does not regulate the deadline for when a divorce permit letter must be issued, while PP Number 45 of 1990 concerning amendments to PP Number 10 of 1983 which is the basis in the Religious Court environment in handling PNS divorce cases including Soldiers regulates the deadline for superiors to provide consideration and continue within a maximum period of three months and SEMA Number 5 of 1984 provides time for Civil Servants to obtain official permission, the trial is postponed for a maximum of 6 (six) months and will not be extended again. Suggestions: The author suggests that Adjustment and Synchronization of Rules are needed between the Religious Court and the TNI, especially the TNI AD, to ensure that divorce procedures run in accordance with applicable regulations. For example, revisions to the TNI Commander Regulation and the Army Chief of Staff Decree to be more in line with SEMA Number 10 of 2020, so that the time given to complete divorce administration is clearer and more consistent.